COVID-19 antibody tests: An overview - Arjun B Ravi; V P Prabath Singh; Roshni Chandran; Krishnan Venugopal; Kaushik Haridas; R Kavitha (Wolters Kluwer Medknow Publications, 2021)
Novel coronavirus (nCoV) first emerged in Hubei province of China in December 2019. The virus initially known as 2019-nCoV was renamed to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) by the International Committee on Taxonomy of Viruses. The associated disease is known as coronavirus disease 2019 (COVID-19). As the COVID-19 pandemic has unfolded, interest has grown in antibody testing as a way to measure how far the infection has spread and to identify individuals who may be immune. Molecular diagnostic tests like polymerase chain reaction are developed rapidly, however they are not able to fulfill all the requirements of an epidemic reaction. Hence, to complement molecular diagnostic tests, serology tests emerged as a vital aspect of the overall response by confirming the presence of antibodies during the early stage of the infection. Antibody tests help in assessing herd immunity, data about the ongoing phase of infection, identifying potential donors for convalescent plasma therapy, etc. This review currently focuses on giving an overview about the antibody tests in SARS-CoV-2 infections.